2018
DOI: 10.1177/0193945918792303
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Ovarian Reserve Within Health Parameters: A Latent Class Analysis

Abstract: The process of ovarian aging is influenced by a complex and poorly understood interplay of endocrine, metabolic, and environmental factors. The purpose of this study was to explore the feasibility of using latent class analysis to identify subgroups based on cardiometabolic, psychological, and reproductive parameters of health and to describe patterns of anti-Müllerian hormone levels, a biomarker of the ovarian reserve, within these subgroups. Sixty-nine lean (body mass index [BMI] ⩽ 25 kg/m) and severely obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The current evidence on the association between BMI and serum AMH levels in women without PCOS is inconclusive but trending toward no relationship. Table 1 summarizes this evidence: 8 studies indicate no association, 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 while 2 found a positive association within at least one cohort 18 , 19 and 4 determined an negative relationship within at least one cohort. 20 , 21 , 22 , 23 A 2020 study by Jaswa et al found that AMH serum levels declined significantly with increasing BMI in the population without obesity (BMI <30 kg/m 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current evidence on the association between BMI and serum AMH levels in women without PCOS is inconclusive but trending toward no relationship. Table 1 summarizes this evidence: 8 studies indicate no association, 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 while 2 found a positive association within at least one cohort 18 , 19 and 4 determined an negative relationship within at least one cohort. 20 , 21 , 22 , 23 A 2020 study by Jaswa et al found that AMH serum levels declined significantly with increasing BMI in the population without obesity (BMI <30 kg/m 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the significant correlation denoted above, other studies' explorations have returned no association. Hardy et al was one of such studies that determined no correlation 11 . However, as obesity has a documented negative impact on fertility, the postpartum status of all patients in Hardy et al is to be noted when considering the generalizability of the cohort's reproductive markers 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the articles included in this systematic review are summarized in Table 5 . Six articles were conducted in the USA [ 28 , 29 , 30 , 31 , 32 , 38 ], two in France [ 42 , 44 ], two in China [ 34 , 43 ], and one each in Taiwan [ 21 ], Australia [ 33 ], Scotland [ 41 ], Turkey [ 45 ], the United Arab Emirates [ 40 ], Israel [ 46 ], India [ 35 ], Brazil [ 36 ], Denmark [ 37 ], and the Philippines [ 39 ]. The mean age of the study participants was 32.3 years.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 The common usage of AMH levels as a measure of fertility necessitates understanding its possible relationship with body mass. Some studies in populations without PCOS have indicated there is no relationship, [10][11][12][13][14][15] while others have found an inverse association. [16][17][18][19][20] The same conflicting results have been found in populations with PCOS, with some studies indicating a negative relationship 12,17,[19][20][21][22] and others not.…”
Section: Introductionmentioning
confidence: 99%